Republic of Congo : Mining Sector Review - World Bank (Washington, DC, 2013)
The Republic of Congo covers an area of 342,000 square kilometers (km), of which forests occupy three-fifths, the rest being dominated by savannah. Oil has long been the principal resource of Congo. Since the first exploitations were launched in 1970, the oil sector has become the dominant economic activity and major source of income for the state. The growth rate in real terms was 8.8 percent in 2010, with gross domestic product (GDP) per capita reaching $4532. In 2010, GDP nearly reached two digit growths, driven up by a significant increase of oil production, by reinforcement of non-oil activities, in particular forest industry, construction and telecommunications. The Government made development of the mining sector a priority to diversify the economy. The present review of the mining sector, led by World Bank in partnership with the Ministry of Geology and Mining, aims to update and understand further these characterizations, to document the prospects and challenges of mining development and to prioritize actions that optimize the sector's contribution to economic diversification and sustainable development. This review of mining sector helped to characterize the issues of governance in following four areas: (1) promotion of geological heritage and mineral resources; (2) facilitating entry into production; (3) continuous improvement of the political, institutional, legal and regulatory framework; and (4) optimization of the sector's contribution to diversification. After this study, an action plan to improve the mining sector can be outlined.